Long-term effect of gastric juice alternating with brushing on the surface roughness, topography, and staining susceptibility of CAD-CAM monolithic materials - da Cruz, Marlon Eduardo Menezes [UNESP]; Oliveira, Jailson Junior Rodrigues [UNESP]; Dovigo, Lívia Nordi [UNESP]; Fonseca, Renata Garcia [UNESP] (Elsevier, 2022)
Statement of problem: Studies on the behavior of computer-aided design and computer-aided manufacturing (CAD-CAM) monolithic materials subjected to gastric juice alternating with brushing—as occurs in patients with bulimia nervosa—are lacking. Purpose: The purpose of this in vitro study was to evaluate, over a simulated 5-year period, the effect of gastric juice alternating with brushing on the roughness, topography, and staining susceptibility of CAD-CAM monolithic materials. Material and methods: Disks of Lava Ultimate (LU), Vita Enamic (VE), IPS Empress CAD (EMP), IPS e.max CAD (EMAX), and Vita Suprinity (VS) were randomly allocated to artificial saliva+brushing or gastric juice+brushing groups, simulating 1, 3, and 5 years of clinical function. The roughness (Sa) and topography were evaluated at baseline (T0) and at each simulated year. For the staining susceptibility (ΔE00), the CIELab color coordinates were registered at baseline, and, at the end of the fifth simulated year, the specimens were immersed in deionized water, coffee, or cola before the second reading. Roughness data were submitted to mixed repeated-measures ANOVA and Bonferroni, and the staining susceptibility data were analyzed by 3-way ANOVA and the Games-Howell test (α=.05). Results: The gastric juice+brushing led to higher roughness than artificial saliva+brushing only in the VE at T3 and T5 (P<.01). In both treatments, the LU and VE showed topography changes and an increase in roughness over time (P<.001), in addition to higher roughness than the other materials (P<.001). The staining susceptibility of the materials to each staining solution was not affected by the treatment (P>.05). The LU and VS groups were more stained by coffee (P<.001), while the VE and EMP groups were more stained by cola (P≤.016), except for the EMP in the gastric juice+brushing, where no significant difference was found between cola and coffee (P>.05). The EMAX was imperceptibly affected by the 3 solutions. Conclusions: Concerning roughness and topography, the LU and VE were the most affected by both treatments. The staining susceptibility of the materials was not affected by the treatment.